Vertical stratification of environmental DNA in the open ocean captures ecological patterns and behavior of deep‐sea fishes. Issue 6 (17th September 2021) - Canals, Oriol; Mendibil, Iñaki; Santos, María; Irigoien, Xabier; Rodríguez‐Ezpeleta, Naiara
Abstract : Establishing the foundations for a sustainable use of deep‐sea resources relies on increasing knowledge on this inaccessible ecosystem, which is challenging with traditional methods. The analysis of environmental DNA (eDNA) emerges as an alternative, but it has been scarcely applied to deep‐sea fish. Here, we have analyzed the fish eDNA contained in oceanic vertical profile samples (up to 2000 m depth) collected throughout the continental slope of the Bay of Biscay. We detected 52 different fish species, of which 25 were classified as deep‐sea fish. We found an increase of deep‐sea fish richness and abundance with depth, and that eDNA reflects day–night community patterns and species‐specific vertical distributions that are consistent with the known diel migratory behavior of many mesopelagic fishes. These findings highlight the potential of eDNA to improve knowledge on the fish species inhabiting the dark ocean before this still pristine ecosystem is further exploited.